(untitled) (American Journal of Pedagogical and Educational Research, 2025)
The article is dedicated to the mechanisms for improving the professional competencies of vocational education teachers based on digital technologies. It analyzes the andragogical framework of continuous professional development and the dynamics of enhancing methodological potential. The results present practical outcomes aimed at improving effective models of professional skills upgrading.